Exosomal Transport of Hepatocyte‐Derived Drug‐Modified Proteins to the Immune System. Issue 5 (29th June 2019) - Ogese, Monday O.; Jenkins, Rosalind E.; Adair, Kareena; Tailor, Arun; Meng, Xiaoli; Faulkner, Lee; Enyindah, Bright O.; Schofield, Amy; Diaz‐Nieto, Rafael; Ressel, Lorenzo; Eagle, Gina L.; Kitteringham, Neil R.; et al.
Abstract : Idiosyncratic drug‐induced liver injury (DILI) is a rare, often difficult‐to‐predict adverse reaction with complex pathomechanisms. However, it is now evident that certain forms of DILI are immune‐mediated and may involve the activation of drug‐specific T cells. Exosomes are cell‐derived vesicles that carry RNA, lipids, and protein cargo from their cell of origin to distant cells, and they may play a role in immune activation. Herein, primary human hepatocytes were treated with drugs associated with a high incidence of DILI (flucloxacillin, amoxicillin, isoniazid, and nitroso‐sulfamethoxazole) to characterize the proteins packaged within exosomes that are subsequently transported to dendritic cells for processing. Exosomes measured between 50 and 100 nm and expressed enriched CD63. Liquid chromatography–tandem mass spectrometry (LC/MS‐MS) identified 2, 109 proteins, with 608 proteins being quantified across all exosome samples. Data are available through ProteomeXchange with identifier PXD010760. Analysis of gene ontologies revealed that exosomes mirrored whole human liver tissue in terms of the families of proteins present, regardless of drug treatment. However, exosomes from nitroso‐sulfamethoxazole‐treated hepatocytes selectively packaged a specific subset of proteins. LC/MS‐MS also revealed the presence of hepatocyte‐derived exosomal proteins covalently modified with amoxicillin, flucloxacillin, and nitroso‐sulfamethoxazole. Uptake of exosomes by monocyte‐derived dendritic cells occurred silently, mainly through phagocytosis, and was inhibited by latrunculin A. An amoxicillin‐modified 9‐mer peptide derived from the exosomal transcription factor protein SRY (sex determining region Y)‐box 30 activated naïve T cells from human leukocyte antigen A*02:01–positive human donors. Conclusion: This study shows that exosomes have the potential to transmit drug‐specific hepatocyte‐derived signals to the immune system and provide a pathway for the induction of drug hapten‐specific T‐cell responses.